TRANSFORMASI ETIKA DIGITAL: MEMBANGUN KEWARGAAN DIGITAL KRITIS (CRITICAL DIGITAL CITIZENSHIP) DI TENGAH HEGEMONI ALGORITMA - Marina Rospitasari; Lailatus Sholihah; Dyah Ayu Kusuma Dewandaru; Wahidah R Bulan; Daffa Rakha Wijaya (GOVERNANCE: Jurnal Ilmiah Kajian Politik Lokal dan Pembangunan, 2026)
The rapid penetration of digital technology, modern society faces an interaction paradox: massive technical connectivity accompanied by increasingly sharp social polarization. This article aims to dissect the failure of conventional digital ethics approaches, which tend to be normative and technical, and offers the Critical Digital Citizenship model as an adaptive solution amidst algorithmic hegemony. Employing a conceptual literature review method, this study synthesizes Mike Ribble's concept of digital citizenship with Paulo Freire's critical pedagogy. The analysis reveals the existence of an "illusion of competence," where users' technical proficiency is not accompanied by critical maturity, thereby creating vulnerability to algorithmic manipulation, disinformation, and data objectification. This study formulates that the "banking concept" approach in digital literacy which solely emphasizes compliance with rules (dos and don'ts) has proven to fail in creating permanent behavioral change because it ignores the users' cognitive and affective dimensions. Therefore, the transformation from naive consciousness to critical consciousness (conscientização) is an absolute prerequisite for building the sovereignty of digital citizens as empowered subjects. The proposed adaptive digital citizenship model emphasizes the integration of critical reasoning to create a society that is not only massively connected but also cognitively enlightened. This article concludes that strengthening critical reasoning within the higher education curriculum is a strategic imperative for realizing a digital civilization that is democratic, cohesive, and resilient to the challenges of the post-truth era.